Pedagogical and Psychological Aspects of The Organization of Person-Oriented Educational Process in Biology Education of General Education Schools - Aripbaev Islambek Muradbаevich; Atashov Ajiniyaz Shaniyazovich (Global Scientific Publishing, 2023)
This article presents opinions about the modernization of the educational system, the use of personalized educational technologies in biology education, and the specific features of personalized technologies. Also, by effectively using the opportunities of individual-oriented educational technologies in biology education, it is necessary to develop the intellectual and creative abilities of students, to awaken in them love for the environment and nature, and to improve the relationship between humanity and nature. Their role in understanding tasks such as setting up a road is highlighted
Keywords: Person-oriented education; formation of individuality of students; modern educational technologies